Framework of life cycle assessment on nutmeg syrup processing. Issue 1 (November 2020) - Trisna; Muhammad; Saptari, M A
Abstract: This study aimed to design the life cycle assessment (LCA) framework on two methods of the nutmeg syrup production process. The difference between those two ways based on how to eliminate tannin in nutmeg flesh, namely: using a salt solvent and albumin. There are three environmental impacts considered in the framework: gas emissions, noise levels, and human energy consumptions. Nutmeg syrup processing has a long process that each step consists of several activities which require resources, including humans, raw materials, water, energy, machine, and tools. The environmental impact needs to be measured for the sustainability of the industry. The stages carried out in this study, including field observations, data collections, establishing LCA framework based on ISO 14044 involving defining goal and scope, identifying inventory analysis, assessing environmental impacts, recommendations for reducing environmental impacts. This LCA framework can be used as the basic to carry out LCA on nutmeg syrup production. A decision-maker can use that LCA result to choose the best production process to reduce environmental impact so they can produce an environmentally sustainable industry.